Design and implementation of an electronic control and image acquisition system for laser scanning confocal microscopy - Gümüş, Gökhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this thesis, an electronic control and image acquisition system for a laser scanning confocal microscope (LSCM) is presented. The system is controlled from a graphical user interface (GUI) via a data acquisition (DAQ) card. GUI is designed and programmed on MATLAB software. Software of the system consists of two parts: generation of the actuation signal and image acquisition and formation. Signals which actuate scanning units to scan the target in LSCM system can be generated by using GUI. The LSCM system is designed in two di erent con gurations: In one con guration, a galvanometer is utilized and in the other one, utilized scanning unit is a 3D printed micro-scanner. Afterwards, image acquisition and display process starts. Two di erent scanning methods, which are raster scanning and Lissajous scanning, are employed to scan the target. Scanning units steer laser beams to the target. Re ected laser beams from the target are acquired by a photo multiplier tube (PMT) that generates current values according to the power of the re ected laser beam. The current values are converted to voltage values using a resistor and then digitized using a DAQ card. The acquired voltage values are mapped between 0 and 255 pixel intensity values according to previously calibrated maximum and minimum voltage values. After all the pixel values are gathered in this manner, a 2D image is constructed and displayed on the GUI of the MATLAB program. Successful operation of the proposed software based GUI system is demonstrated by constructing images from USAF 1951 negative resolution test target. Additionally, successful results on specimens like onion epidermal cells, red blood cells, bacteria cells, yeast cells, chicken skin are provided.In order to improve image quality, denoising with wavelets is applied on resulting images.
Keywords: Electronic control.; Confocal microscopy.